Hawaiʻi at the crossroads of the U.S. and Japan before the Pacific War - Davidann, Jon Thares, 1961- (University of Hawai'i Press, 2008)
This text tells the story of Hawaii's role in the emergence of Japanese cultural and political internationalism during the interwar period. It explores US-Japanese conflict and cooperation in Hawaii.